Study on the effect of new type liquid accelerator on the performance of shotcrete (Fracture and Structural Integrity, 2017)
Shotcrete is an essential preliminary support means in New Austrian Tunneling Method (NATM) construction and plays a very important role in controlling the stability of surrounding rock. The accelerator is a necessary admixture in shotcrete and its quality can greatly affect shotcrete performance. This paper proposes a new liquid accelerator characterized by short initial and final setting time, small dosage, and good adaptability to cement. Laboratory tests and field tests are conducted to verify the influence of this liquid accelerator on performance of shotcrete. Numerical simulation is carried out to study the strength growth of shotcrete with time and interaction between the strength and stress release of surrounding rock. The results show that the initial and final setting time of this liquid accelerator is 2 minutes and 4 minutes respectively. Its dosage is just 1.5% to 4% of the cement quantity. Adding this liquid accelerator can effectively improve the early strength and reduce the later strength loss of shotcrete, and therefore enhance the supporting effects of shotcrete on surrounding rock. In the field application, it is an ideal liquid accelerator for shotcrete, characterized by little resilience, no slurry shedding, and low dust.
Keywords: Liquid accelerator; Shotcrete; Primary support; Stress release of surrounding rock; Numerical simulation